Posthuman Ecologies: Complexity And Process After Deleuze. Rethinking Environmental Ethics In The Age Of Ai And Biotechnology (International Journal of Environmental Sciences, 2025)
It is as if humanity is being confronted with the ultimate pairing of ecological crisis and technological transformation. Climate change and a catastrophic rate of loss of biodiversity imperil the integrity of natural systems at the same time as advances in artificial intelligence (AI) and biotechnology transform our existence. Anthropocentric environmental ethics, which focus on human interests, seem insufficient to respond to these interlocking challenges. To that end, this articles uggests a posthuman ecologies approach, which combines critiques of posthumanist theory with environmental science to reconceptualize environmental ethics for an era of AI, biotechnology, and climatic endtimes. We discuss relevant literature in the field of environmental ethics and critical posthumanism, presenting a theoretical approach that decenters the human and casts moral regard across non-human life and non-life actants, and between biological and non-biological actants. We then examine in a critical perspective the crossing of AI and biotechnology and how these intersect with ecological collapse, and we map their possible returns and dangers from a posthumanist point of view. The regime of ethical inclusion we advocate is one that takes account of the agency of human and nature-technological entities and designs ways of life accordingly. At the heart of these debates is the question as to how a post-anthropocentric, interdisciplinary paradigm can and must shape the future of the climate crisis and the direction of technology towardsecological sustainability. The paper suggests that reconceptualising environmental ethics through posthumanist approaches can help to support more robust, equitable and ecologically sensitive responses to global environmental change.